(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This article describes the design of Tashkent highways, construction and operation, construction of ecologically modern landscape structures along highways. Road greening in the article methods, technologies, modern and foreign experience and techniques and their application is fully covered.